Managing lean success : a warehouse balancing act. B - Yue, Tao, active 2022, (SAGE Business cases., 2020)
CEVA decided that in order to sustainably meet its service obligations to Uniqlo, the company needed to return to its core value of putting its people first, which is the foundation of lean management. Instead of opting for the short-term solution of top-down management, CEVA invested in transformational (worker-centric) leadership. This allowed CEVA the production flexibility it needed to be able to handle the variations in warehouse volumes. Uniqlo renewed its contract with CEVA in 2017, and growth in business was expected to continue. In 2018, CEVA and Uniqlo were already starting negotiations for the next agreement. However, gradual changes in labour force demographics meant that CEVA was beginning to face new challenges – namely, how to ensure that it had enough shop floor workers to keep up with its ever-increasing production requirements, how to balance its employees interests with those of the growing trend of automation, and how to do so in accordance with its sustainability ambitions.